Effect of soil sterilisation on biological control of Fusarium oxysporum f. sp. lycopersici and Meloidogyne javanica by antagonistic fungi and organic amendment in tomato crop - M. W. Mwangi; W. M. Muiru; R. D. Narla; J. W. Kimenju; G. M. Kariuki (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2018)
One of the major challenges in the application of biological control agents into the soil is their inability to withstand competition from natural microflora. In this study a management programme involving fungal biological control agents Trichoderma harzianum (TH) and Purpureocillium lilacinium (PL), and the organic amendment neem was carried out for the control of Meloidogyne javanica and Fusarium oxysporum f. sp. lycopersici (FOL). The experiment was carried out in sterile and non-sterile soil in order to test the efficacy of biological control in natural soil conditions. This experiment was repeated twice. A Wilcoxon's Signed-Rank test indicated there were no significant (P < 0.05) differences in fusarium wilt control in sterile and non sterile soils in the treatments PL neem and TH neem, but there was significantly (P < 0.05) higher control of M. javanica in the same treatments in sterile soils compared to non sterile soils. The combinations of fungal antagonists and neem were effective in non sterile as in sterile soils in the control of fusarium wilt, while being less effective in the control of M. javanica. Thus the biological control agents can be very effective in the control of fusarium wilt in natural conditions where the soil is not sterilised, but be less effective in the control of M. javanica in the same conditions. There is therefore potential of integrated management of fusarium wilt and root-knot nematodes (RKN) by these biological control agents in natural soil field conditions as an alternative to using chemicals.